The Fiqh Scholars Disclosure on Crewman Boat Friday Prayers - Yaqub, Andi; Jamaluddin, Mohd Hafiz; Aulia, Andi Fahrunnisa (Mazahibuna: Jurnal Perbandingan Mazhab, 2023)
This research aims to investigate the responsibility of serving as a resource for crew members on the boat of a captain, with reference to the traditional school of law in Islamic jurisprudence known as fiqh. Specifically, the focus is on the obligation of Friday prayers for the crew and the different opinions on this matter based on the fiqh madhhab. This research is conducted through a comprehensive review of relevant literature. Primary and secondary data were collected using a descriptive qualitative research method, with the Qur'an and Hadith serving as the primary sources of information. The results showed that Friday prayers are mandatory for Muslim men who meet the requirements and have no old syar'ī. However, there are varying opinions among Muslim Imams regarding the performance of Friday prayers for crew members on board. The Maliki and al-Shafi'i madhhabs of thought believe that Friday prayers are invalid when they are not conducted in a mosque, while the Hanafi and Hambali madhhabs permit Friday prayers to be performed anywhere. Regarding the permissibility of praying on a ship, Imam Abu Hanifah believes it is acceptable to pray on a boat or ship when it is on land. When the ship is not in a confined state on the ground at the port and it is possible to leave the ship, it is forbidden to pray on it. Meanwhile, Imam Malik and Imam al-Shafi'i hold that it is permissible to pray on a ship, even when it is conceivable to leave the ship, as long as the prayer is performed facing the Qibla and its pillars are perfect. Imam Ahmad bin Hambal is of the opinion that it is not permissible to conduct the fardu prayer on a ship if the individual is able to perform the prayer outside the ship.